“Oral Expression in the classroom”Program for the development of oral expression and comprehension of the English Language - Ferro Quintanilla, Daisy Rebeca (2017)
The purpose of this research was to determine the effectiveness of the “Oral Expression in the Classroom”program in the development of the Oral Expression and Comprehension of the English language in the second year of secondary education. This research is basic of a quantitatively approach, which design was pre-experimental, and participants were 14 students. For this study’s development, it was necessary to elaborate an instrument which was validated by experts in this area. The analysis of the results through the “T”test showed significant differences (p <0.05) in the Oral Expression and Comprehension Variable, where results were obtained, with an average of an early 28.07 compared to 51.79 later, which average difference is 23.714. These results corroborate the effectiveness of the program, showing that participants improved significantly in pronunciation, grammatical and lexical accuracy, oral interaction, body language and communicative understanding, to communicate in English. Also, all the above-mentioned results showed that the students were able to interact with their classmates and to develop easily the communication process.